Plant, Soil and Microbes 2016
DOI: 10.1007/978-3-319-29573-2_3
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Functional Analyses of SWEETs Reveal Cues for Their Role in AMF Symbiosis

Abstract: SWEETs are novel class of sugar effl uxers, which have unique functional role in plant biology. Besides nectar production, freezing tolerance, and transport of hexoses across tonoplast and growth-supporting role of pathogens, these SWEETs could have potential role in establishing powerful symbiotic relationship at the root interface and also in feeding to arbuscular mycorrhizal fungi (AMF) symbionts. The microarray or transcriptome expression of SWEET genes from colonized roots revealed that out of 28 Medicago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, four of the eight orthologs, SWEET4c , SWEET6 , SWEET11b and SWEET14 , were expressed in the panicle tissues in sorghum [ 78 ], indicating that these 4 genes take part in sugar transport for reproductive rather than vegetative growth. Two of the rice orthologs, SWEET3b and SWEET12 were induced by arbuscular mycorrhizal fungi (AMF) symbiosis in the root tissues [ 83 ], indicating that SWEET3b and SWEET12 could have potential functions in creating symbiotic relationships at the root interface.…”
Section: Discussionmentioning
confidence: 99%
“…However, four of the eight orthologs, SWEET4c , SWEET6 , SWEET11b and SWEET14 , were expressed in the panicle tissues in sorghum [ 78 ], indicating that these 4 genes take part in sugar transport for reproductive rather than vegetative growth. Two of the rice orthologs, SWEET3b and SWEET12 were induced by arbuscular mycorrhizal fungi (AMF) symbiosis in the root tissues [ 83 ], indicating that SWEET3b and SWEET12 could have potential functions in creating symbiotic relationships at the root interface.…”
Section: Discussionmentioning
confidence: 99%
“…We found that SWEET3.3 and SWEET12 were more strongly upregulated in Ri09-colonized roots ( Fig. 7F ); both are upregulated in arbusculated cortical cells in M. truncatula (Sameeullah et al 2016). Interestingly, SWEET7 and SWEET13 were more strongly induced in Ga165-colonized roots, but SWEETs perform diverse physiological functions, and their upregulation does not necessarily increase sugar transport to the fungus.…”
Section: Discussionmentioning
confidence: 87%
“…SWEET proteins are pH-independent, bidirectional ST with broad representation in bacteria, plants, fungi and animals (Chen et al, 2010; Chen et al, 2012; Lin et al, 2014) with crucial roles in multiple biological processes. SWEET1b shows upregulation in M+ plants, similar to the rice gene OsSWEET1b (Samueelah et al, 2016) or potato genes StSWEET1a and StSWEET1b (Manck-Götzenberger & Requena, 2016). Closest characterized homologue is AtSWEET1 of thale cress ( Arabidopsis thaliana ), whose substrate specificity is higher for Glc and somewhat lower for Gal, but does not transfer Suc (Chen et al, 2010), so similar substrate specificity could be expected for SWEET1b as well.…”
Section: Discussionmentioning
confidence: 90%